1972
DOI: 10.1021/jo00970a010
|View full text |Cite
|
Sign up to set email alerts
|

o-Styrylnitrene route to 2-substituted indoles. Pyrolysis of o-azidostyrenes

Abstract: The utility of o-azidostyrene derivatives as indole precursors via o-styrylnitrenes has been examined. The cyclization proceeds efficiently for /3-alkyl-and /S-aryl-o-azidostyrenes and is also satisfactory for /3-acyl-o-azidostyrenes. A synthesis of 2-acylindoles involving two steps, base-catalyzed condensation of a methyl ketone with o-azidobenzaldehyde and pyrolysis to the indole, was carried out successfully in five cases with yields from 21 to 73%. These yields are generally superior to yields of 2-acylind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…Ortho ‐alkenyl aryl azides also rearrange to indoles upon heating. This reaction, known as the Sundberg cyclization,331, 332 takes place by direct attack at the β‐carbon atom and not after insertion into the CH bond 332. This reaction was recently applied to the synthesis of complex indoles (Scheme ) 333335.…”
Section: Reactions Of Organic Azidesmentioning
confidence: 99%
“…Ortho ‐alkenyl aryl azides also rearrange to indoles upon heating. This reaction, known as the Sundberg cyclization,331, 332 takes place by direct attack at the β‐carbon atom and not after insertion into the CH bond 332. This reaction was recently applied to the synthesis of complex indoles (Scheme ) 333335.…”
Section: Reactions Of Organic Azidesmentioning
confidence: 99%
“…In our first report, 7b no alkyl- or aryl group migration was observed for styryl azides with β-hydrogen substituents (entry 1). Our subsequent study revealed that aryl groups migrate in preference to alkyl groups (entry 2).…”
mentioning
confidence: 90%
“…3–5 While nitro group migrations have been observed in isolated cases, 6 these transformations have not been harnessed for the regioselective synthesis of nitro-substituted N -heterocycles. Styryl azides are established as useful indole precursors, 7 and our group has previously reported that Rh 2 (II) octanoate catalyzes a phenyl group migration to transform β,β-diphenylstyryl azide into 2,3-diphenylindole. 2b When the styryl azide contains a β-hydrogen, a C–H amination reaction occurs: thermolysis of β-nitro-substituted 1 was reported by Gribble and co-workers to produce 2-nitroindole 2 as the major product (eq 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After the evolution of nitrogen stopped, the excess AlCl 3 was destroyed by 10% NaOH and after purification on silica gel plates, we isolated trans-2-aminostilbene, mp 101-103 °C 13 , (formed by triplet nitrenium ion hydrogen atom abstraction) in 45% yield and only traces of 3. Thermolysis of 1 in ethylene glycol (reflux for 4 h) also furnished the 2-phenyl-1H-indole in 87% yield but in this case the intermediate is a nitrene 12 . Decomposition of 1, either in acidic conditions or by thermolysis, gave 2-phenyl-1H-indole 3 with comparable yields.…”
Section: Resultsmentioning
confidence: 95%